Effect of Gamma Irradiation on the Microbial Quality of Dried Fishes - Prakash, Sinduja; Jeyasanta K, Immaculate; Edward, J.K Patterson; Patterson, Jamila (The Asia Journal of Applied Microbiology, 2014)
Sun dried fishes such as C. malabaricus, S. lysan, S. acutipinnis, L. dussumieri, L. platypterus, L. rubrioperculatus and A. thazard were irradiated using gamma radiation (5 kGy) and the microbial quality and shelf life were assessed in the irradiated and non-irradiated dry fish samples stored under ambient temperature for six months. Irradiation had significant effects on the reduction of microbial population. The total bacterial count in was in acceptable condition until the end of the sixth months of storage. Total fungal counts were below detectable level throughout the storage period. Growth of Salmonella and Vibrio were observed in the non- irradiated samples where as it was not observed in the irradiated dry fishes.